PENGARUH METODE AT-TARTIL TERHADAP KEMAMPUAN SANTRI DALAM MEMBACA AL-QUR’AN ‎DI LEMBAGA BMQ AT-TARTIL PONDOK PESANTREN KANZUL ULUM TAHUN AJARAN 2023–2024 - Aida Fitriani; Nikmatun wafiroh; Junaidi (Wasīlah: Journal Of Sharia Sciences, 2026)
This study aims to examine the effect of the At-Tartil Method on the Quranic reading ‎ability of students at BMQ At-Tartil Institution of Kanzul Ulum Islamic Boarding School in ‎the 2023–2024 academic year. The study employs a quantitative approach with an ex post ‎facto research design. Stratified random sampling was used to select participants, and data ‎were analyzed using simple linear regression. The independent variable (X) was the ‎application of the At-Tartil Method, and the dependent variable (Y) was students’ Quranic ‎reading ability. Results revealed t-value = 4.435 > t-table = 1.703 and F-value = 19.673 > F-‎table = 3.34, with a regression equation of Y = 29.032 + 0.642X. These findings confirm that ‎the At-Tartil Method has a significant positive influence on students’ Quranic reading ‎ability. This study contributes theoretically to the development of Quranic learning ‎methods in Islamic boarding school settings and provides practical recommendations for ‎Quranic education institutions.‎